PELAKSANAAN METODE RESITASI UNTUK MENGERJAKAN TUGAS DARING OLEH SISWA DI SMAN 7 PADANG PADA MATA PEMBELAJARAN GEOGRAFI - WIRANDA WIRANDA; Nofrion Nofrion (JURUSAN GEOGRAFI FIS UNP, 2023)
The purpose of this study is to describe what are the obstacles for class XI IPS 1 students in implementing the recitation method for doing online assignments for geography lessons. This research was conducted at SMA Negeri 7 Padang. This research is a qualitative research with descriptive method. Data obtained from observations, interview and documentation. The subjects of this study were teachers of geography lessons and students of class XI IPS 1 with the technique of taking the subject using the Snowball Sampling Technique. Based on data analysis, it is known that the obstacles faced by students in doing online assignments using the recitation method are the limitations of students' internet quotas, sometimes a sudden power outage, and lack of understanding of students with learning materials. Efforts made include the teacher giving time for students who are constrained by the network, waiting for the PLN electricity light to turn on, and teachers must always motivate students to diligently read the material. Provision of internet quota from the Ministry of Education and Culture. Keywords : Recitation Method, Online Assignments, Geography Courses